2015
DOI: 10.1136/bjophthalmol-2014-306019
|View full text |Cite
|
Sign up to set email alerts
|

Do pattern deviation values accurately estimate glaucomatous visual field damage in eyes with glaucoma and cataract?

Abstract: Clinicians should be very careful when reviewing the VF of a patient with glaucoma and cataract since PD values may underestimate glaucomatous VF damage in patients with advanced disease and also overestimate glaucomatous VF damage in patients with early to moderate cataract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Moreover, a previous study has reported that eye movement of less than 38 are commonly observed in VF tests, even in well-trained healthy observers. 4,21 The relationship between PSD and MD can be explained using a quadratic linear regression model, 16,22 where PSD decreases in the moderate to advanced stages of the disease. 7 PSD was included as a predictor of MD in the best linear model in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a previous study has reported that eye movement of less than 38 are commonly observed in VF tests, even in well-trained healthy observers. 4,21 The relationship between PSD and MD can be explained using a quadratic linear regression model, 16,22 where PSD decreases in the moderate to advanced stages of the disease. 7 PSD was included as a predictor of MD in the best linear model in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Matsuda et al [10] compared visual fields in glaucoma patients before and after cataract surgery to ascertain the role of cataracts themselves in standard visual field metrics. They note that total deviation on visual fields in patients with cataracts improves significantly after surgery, suggesting that total deviation alone may not be a sufficient metric to assess glaucoma severity in eyes with cataracts.…”
Section: Cataract Extraction and Visual Fieldsmentioning
confidence: 99%
“…But this general correction may not always be appropriate. Removing all diffuse VF loss in pattern deviation values may underestimate glaucomatous VF damage in some patients with advanced VF damage 22 . Therefore we analyzed both plots.…”
Section: Discussionmentioning
confidence: 99%